Chitinophilic and keratinophilic fungi as a source of secondary metabolites / Siti Nur Sarah Zubir - Zubir, Siti Nur Sarah (2017)
ABSTRACT Fungi, recognised as frequent producers of secondary metabolites, occupy virtually all possible ecological niches. The present study focuses on studying chitinophilic and keratinophilic fungi as a potential source of secondary metabolites. The main objective of this study was to isolate secondary metabolites from the above-mentioned fungi using a modified version of the protocol named MECSUS (Microtiter plate, Elicitors, Combination, Solid phase extraction, UHPLC, Statistical analysis), which was recently developed in the Microbial Metabolite Laboratory of Atta-ur-Rahman Institute for Natural Products Discovery (AuRIns). Putative chitinophilic fungi were isolated by collecting insects that were sick or dead and showing signs of fungal infection, while presumed keratinophilic fungi were obtained using the 'Tokava' hairbaiting method on soil samples collected from the Biological Research of AuRIns at Puncak Alam (Selangor), a fish sanctuary at Sungai Chilling (Selangor), the EndauRompin National Park (Johor) and Tanah Aina at Bentong (Pahang). Fifteen fungi were isolated, namely Penicillium sp. (TOWB-F2), Trichoderma virens (SA-F1), Gliomastix polychroma (SC14a-1), Fusarium solani (SC14a-2), Penicillium sp. (SC14b-1), Pseudallescheria boydii (ERS), Fusarium decemcellulare (ERI), Boeremia exigua (ER2a-1), Nigrospora oryzae (ER2a-2), Wardomyces moseri (ER2b1), and Purpureocillium lilacinum (BENTONG) and unidentified species (TOWB-F1, TOWB-F3, 5FS-F1, TOH). A growth study was conducted over a month on the first five isolated fungi (i.e. TOWB-F1, TOWB-F2, TOWB-F3, SA-F1 and 5FS-F1) to determine the suitable duration of fermentation. The isolated fungi were grown simultaneously on 96-well microtiter plates in 8 media made of a common standard composition and supplemented with various elicitors. Liquid-liquid extraction was used to extract the secondary metabolites from the cultures. The crude extracts were analysed by HPLC. Selected extracts were fractioned until pure compound were obtained. Spectroscopic analysis was performed using nuclear magnetic resonance (NMR), ultraviolet (UV), and mass spectrometry (MS) to elucidate the structure of pure compounds. Four compounds were isolated during this study that is penicillic acid, pseurotin A, patulin and javanicin